Indian trade unions - Karnik, V. B. (Bombay, 1966)
This is a broad and cursory survey of the trade union movement as it has developed in India during the last forty years. survey is obviously not exhaustive as the object was to indicate The the main trends rather than to note all details. It is hoped that, howsoever imperfect, it will prove of some use to trade union workers as well as to others interested in the trade union movement. The free and democratic trade union movement that is deve loping in the country has yet to face many problems and cross many hurdles. A free and frank discussion of those problems and hurdles, in the light of experiences made by the movement, may help it to face them with confidence. The survey that I have attempted will, I hope, contribute to that discussion.
Keywords: Trade - unions - India